Managing Potential and Realized Absorptive Capacity: How do Organizational Antecedents Matter? - Jansen, Justin J. P.; Van Den Bosch, Frans A. J.; Volberda, Henk W. (Academy of Management Journal, 2005)
Exploring how organizational antecedents affect potential and realized absorptive capacity, this study identifies differing effects for both components of absorptive capacity. Results indicate that organizational mechanisms associated with coordination capabilities (cross-functional interfaces, participation in decision making, and job rotation) primarily enhance a unit's potential absorptive capacity. Organizational mechanisms associated with socialization capabilities (connectedness and socialization tactics) primarily increase a unit's realized absorptive capacity. Our findings reveal why units may have difficulty managing levels of potential and realized absorptive capacity and vary in their ability to create value from their absorptive capacity.